ANALYSIS OF STUDENTS' LITERACY ABILITY IN UNDERSTANDING HOTS QUESTIONS IN GRADE V AT MIN 3 MATARAM - Hajrah (Sinar Lima, 2026)
This research is motivated by students' literacy skills in understanding HOTS questions. This study aims to determine students' literacy skills, their ability to understand HOTS questions, and the obstacles they face in understanding HOTS questions in grade V at MIN 3 Mataram City. This study used a descriptive qualitative approach. The study was conducted at MIN 3 Mataram City in the 2024/2025 academic year. Data collection methods used were interviews, non-participant observation, and documentation. The data analysis process used was data reduction, data presentation, and conclusions or verification. Data validity was verified using extended observation and research, triangulation, and reference coverage. The results of this study indicate that grade VA students demonstrated low literacy skills in answering HOTS questions based on the ability indicators of analyzing (C4), evaluating (C5), and creating (C6). The largest number of students (22, 67%) fell into the low HOTS category, followed by 7 (21%), and only 4 (12%). Challenges experienced by grade VA students at MIN 3 Mataram City in understanding HOTS questions include a lack of understanding of the material and instructions. This is due to teachers rarely giving HOTS-based questions to students, who only provide HOTS questions when they are included in the worksheet.